Anti‐CD25 monoclonal antibody Fc variants differentially impact regulatory T cells and immune homeostasis. Issue 3 (12th May 2016) - Huss, David J.; Pellerin, Alex F.; Collette, Brian P.; Kannan, Arun K.; Peng, Liaomin; Datta, Abhishek; Wipke, Brian T.; Fontenot, Jason D.
Summary: Interleukin‐2 (IL‐2) is a critical regulator of immune homeostasis through its non‐redundant role in regulatory T (Treg) cell biology. There is major interest in therapeutic modulation of the IL‐2 pathway to promote immune activation in the context of tumour immunotherapy or to enhance immune suppression in the context of transplantation, autoimmunity and inflammatory diseases. Antibody‐mediated targeting of the high‐affinity IL‐2 receptor α chain (IL‐2R α or CD25) offers a direct mechanism to target IL‐2 biology and is being actively explored in the clinic. In mouse models, the rat anti‐mouse CD25 clone PC61 has been used extensively to investigate the biology of IL‐2 and Treg cells; however, there has been controversy and conflicting data on the exact in vivo mechanistic function of PC61. Engineering antibodies to alter Fc/Fc receptor interactions can significantly alter their in vivo function. In this study, we re‐engineered the heavy chain constant region of an anti‐CD25 monoclonal antibody to generate variants with highly divergent Fc effector function. Using these anti‐CD25 Fc variants in multiple mouse models, we investigated the in vivo impact of CD25 blockade versus depletion of CD25 + Treg cells on immune homeostasis. We report that immune homeostasis can be maintained during CD25 blockade but aberrant T‐cell activation prevails when CD25 + Treg cells are actively depleted. These results clarify the impact of PC61 on Treg cell biology and reveal an important distinction between CD25 blockade and depletion of CD25 + Treg cells. These findings should inform therapeutic manipulation of the IL‐2 pathway by targeting the high‐affinity IL‐2R.